Data-driven spatio-temporal modelling of glioblastoma. Issue 3 (22nd March 2023) - Jørgensen, Andreas Christ Sølvsten; Hill, Ciaran Scott; Sturrock, Marc; Tang, Wenhao; Karamched, Saketh R.; Gorup, Dunja; Lythgoe, Mark F.; Parrinello, Simona; Marguerat, Samuel; Shahrezaei, Vahid
Abstract : Mathematical oncology provides unique and invaluable insights into tumour growth on both the microscopic and macroscopic levels. This review presents state-of-the-art modelling techniques and focuses on their role in understanding glioblastoma, a malignant form of brain cancer. For each approach, we summarize the scope, drawbacks and assets. We highlight the potential clinical applications of each modelling technique and discuss the connections between the mathematical models and the molecular and imaging data used to inform them. By doing so, we aim to prime cancer researchers with current and emerging computational tools for understanding tumour progression. By providing an in-depth picture of the different modelling techniques, we also aim to assist researchers who seek to build and develop their own models and the associated inference frameworks. Our article thus strikes a unique balance. On the one hand, we provide a comprehensive overview of the available modelling techniques and their applications, including key mathematical expressions. On the other hand, the content is accessible to mathematicians and biomedical scientists alike to accommodate the interdisciplinary nature of cancer research.